Perdas quantitativas na colheita mecanizada de soja em diferentes condições operacionais de duas colhedoras - Magalhaes, Stefania Caixeta [UNESP]; Oliveira, Beatriz Costa; Toledo, Anderson [UNESP]; Tabile, Rubens Andre [UNESP]; Silva, Rouverson Pereira [UNESP] (Universidade Federal de Uberlândia (UFU), 2009)
Mechanized harvesting losses are one of the main problems in the soybean production. This work aimed characterize the quantitative losses of productivity for area, in the mechanized harvesting system in commercial production soybean grains, in function of harvesting displacement speed and year of production. The test was accomplished using a randomized design in a fatorial scheme 2x2, being treatments composed by two harvesting operating in two speeds, 4,0 a 4,5 km h(-1) and 6,0 a 7,0 km h(-1), with five replications for each treatment. The harvesting used Massey Ferguson 5650 Advanced, year of production 2003 e Massey Ferguson 5650 Advanced, year of production 2004. They were evaluated the soybean grains losses caused by the cleaning and separation systems, cut deficiency in the harvesting cutterhead and total losses. The results showed the losses of systems of separation was influenced by harvesting, and the others variables are not significative alterations and the losses in the systems of cleaning showed more contribution for the total losses.

A perda de grãos durante a colheita mecanizada está entre os principais problemas encontrados na produção de soja. Diante disso, este trabalho objetivou caracterizar as perdas quantitativas no sistema de colheita mecanizada em área de produção comercial de grãos de soja, em função da velocidade de deslocamento e do modelo das colhedoras. A colheita foi realizada utilizando-se delineamento inteiramente casualizado, em esquema fatorial 2x2, sendo os tratamentos compostos por dois modelos de colhedoras operando em duas velocidades de deslocamento, 4,0 a 4,5 km h-¹ e de 6,0 a 7,0 km h-¹, com cinco repetições. Foram utilizadas colhedoras Massey Ferguson 5650, Advanced, ano 2003 e Massey Ferguson 5650, ano 2004. Foram avaliadas as perdas de grãos de soja ocasionadas pelos sistemas de limpeza, de separação, por deficiência de corte na plataforma da colhedora e as perdas totais. Concluiu-se as perdas no sistema de separação foi influenciada pela colhedora, as demais variáveis não tiveram alterações significativas e que as perdas no sistema de limpeza apresentaram maior contribuição para as perdas totais.
Quantitative losses in the soybean mechanized harvesting in different operational conditions of two harvesters
Keywords: Harvesting; speed; Glycine max